2016
DOI: 10.1016/j.phytol.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Beilschglabrines A and B: Two new bioactive phenanthrene alkaloids from the stem bark of Beilschmiedia glabra

Abstract: Beilschglabrines A and B: Two new bioactive phenanthrene alkaloids from the stem bark of Beilschmiedia glabra http://researchonline.ljmu.ac.uk/3608/ Article LJMU has developed LJMU Research Online for users to access the research output of the University more effectively. Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Users may download and/or print one copy of any article(s) in LJMU Research Online to facilitate their private stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The isolated terpenoids were also reported most of the Piper species. They were readily identified by comparison of physical and spectroscopic data and mass spectrometry data with values found in the literature (Salleh et al, 2016a;Salleh et al, 2016b).…”
Section: Resultsmentioning
confidence: 95%
“…The isolated terpenoids were also reported most of the Piper species. They were readily identified by comparison of physical and spectroscopic data and mass spectrometry data with values found in the literature (Salleh et al, 2016a;Salleh et al, 2016b).…”
Section: Resultsmentioning
confidence: 95%
“…The chemical structures are shown in Figure 1. In addition, lupeol (7) [9], lupenone (8) [10], β-sitosterol (1) [11], and β-sitostenone (2) [12] were also identified. All secondary metabolites were identified by analyzing their spectroscopic data and comparing them with the literature data.…”
Section: Resultsmentioning
confidence: 99%
“…AChE inhibition (I%) 5,7-Dimethoxyflavone (3) 47.5% 4,5,7-Trimethoxyflavone (4) 52.8% 3',4',5,7-Tetramethoxyflavone (5) 58.2% 5-Hydroxy-7-methoxyflavone (6) 25.5% 5-Hydroxy-4ʹ,7-dimethoxyflavone (9) 24.2% Galantamine b…”
Section: Samplesmentioning
confidence: 99%
“…The genus produces several classes of compounds such as terpenoids, endiandric acid derivatives, essential oils, fatty acids, epoxyfuranoid lignans, flavonoids, and alkaloids. Some of these compounds are reported to exhibit antioxidant, antibacterial, antimalarial and antituberculosis activities (Chen et al, 2007;Lenta et al, 2009;Chouna et al, 2010;Salleh et al, 2015b;Salleh et al, 2016a;Salleh et al, 2016b;Salleh et al, 2016c;Salleh et al, 2016d). Previous studies on the compositions of the essential oils of Beilschmiedia species have been reported on B.…”
Section: Introductionmentioning
confidence: 99%